Distinct Hypericum perforatum L. total extracts exert different antitumour activity on erythroleukemic K562 cells. (22nd May 2018) - Valletta, Elena; Rinaldi, Annamaria; Marini, Mario; Franzese, Ornella; Roscetti, Gianna
Abstract : Total flower extracts of Hypericum perforatum L. obtained with 3 different solvent systems were tested on tumour cell line cultures by comparing two groups of plants harvested in different times and places. The extracts, characterized according to the spectroscopic profile and the hypericin content, were tested on the growth and apoptotic death of K562 cells, a human erythroleukemic cell line. Growth and apoptosis were analysed by viable cell count, flow cytometry, and fluorescence microscopy at 6, 24, and 48 hr of culture following 1 hr exposure to the extracts under investigation. Here, we show that Hypericum extracts are able to reduce the growth of K562 cells and induce different degrees and kinetics of apoptosis according to the group of plants of origin. Also, we highlighted interesting differences in terms of efficacy among the extracts, with some samples losing their effectiveness along the culture time and others able to maintain or even increase their efficacy. Furthermore, the data herein obtained confirm the role of non hypericin compounds that are present in different proportions in the two plant groups and in the extracts analysed.